Air Pollution as a Potential Determinant of Rheumatoid Arthritis: A Population-based Cohort Study in Taiwan. (October 2017) - Jung, Chau-Ren; Hsieh, Hui-Ya; Hwang, Bing-Fang
Abstract : Background: Limited studies have explored the relationship between air pollution and rheumatoid arthritis (RA), with the results being somewhat inconsistent. Methods: This was a retrospective cohort study that included 322, 301 subjects aged 30–50 years, selected from the National Health Insurance Research Database in Taiwan, were followed from 2001 to 2010. We used a time-dependent extended Cox model and incorporated time-dependent variables to estimate the associations between the annual mean concentrations of air pollutants with RA, including carbon monoxide (CO), nitrogen dioxide (NO2 ), ozone (O3 ), particles with an aerodynamic diameter less than 10 μm (PM10 ), and sulfur dioxide (SO2 ), and reported the hazard ratio (HR) and 95% confidence interval (CI). Results: Newly diagnosed RA was positively associated with a 100-ppb increase in CO (adjusted HR = 1.17 [95% CI = 1.16, 1.18]), a 10-ppb increase in NO2 (1.54 [1.45, 1.64]), a 10-ppb increase in O3 (1.37 [1.33, 1.41]), and a 1 ppb in SO2 (1.02 [1.00, 1.04]). There was no association between a 10-μg/m 3 increase in PM10 and RA (1.02 [0.99, 1.05]). Conclusions: Our finding suggests that O3 and traffic-related air pollutants (CO and NO2 ) may be positively associated with incident RA. This is an important finding given that many individuals are exposed to similar levels of O3 and NO2 globally.